Stelsels substitutie (reeks 2)

Hoofdmenu Eentje per keer 

Substitutie

  1. \(\left\{\begin{matrix}3x-5y=\frac{269}{42}\\3x=-y+\frac{-151}{42}\end{matrix}\right.\)
  2. \(\left\{\begin{matrix}-3x+2y=\frac{-27}{14}\\-6x=y+\frac{-3}{28}\end{matrix}\right.\)
  3. \(\left\{\begin{matrix}-x+3y=\frac{-85}{3}\\6x-6y=50\end{matrix}\right.\)
  4. \(\left\{\begin{matrix}4y=\frac{-217}{13}-2x\\x-2y=\frac{225}{26}\end{matrix}\right.\)
  5. \(\left\{\begin{matrix}3x+2y=\frac{88}{35}\\x-2y=\frac{-144}{35}\end{matrix}\right.\)
  6. \(\left\{\begin{matrix}-3y=\frac{-389}{33}-4x\\-2x+y=\frac{181}{33}\end{matrix}\right.\)
  7. \(\left\{\begin{matrix}6x+3y=\frac{-162}{19}\\x=-3y+\frac{-67}{19}\end{matrix}\right.\)
  8. \(\left\{\begin{matrix}3y=13-4x\\-5x+y=\frac{32}{3}\end{matrix}\right.\)
  9. \(\left\{\begin{matrix}6x+4y=\frac{-446}{35}\\-x=-4y+\frac{9}{35}\end{matrix}\right.\)
  10. \(\left\{\begin{matrix}-6y=\frac{205}{13}+x\\6x+3y=\frac{-1032}{13}\end{matrix}\right.\)
  11. \(\left\{\begin{matrix}-6x-y=\frac{-331}{65}\\4x-4y=\frac{1852}{195}\end{matrix}\right.\)
  12. \(\left\{\begin{matrix}-x+4y=\frac{-39}{5}\\4x=-3y+\frac{263}{20}\end{matrix}\right.\)

Substitutie

Verbetersleutel

  1. \(\left\{\begin{matrix}3x-5y=\frac{269}{42}\\3x=-y+\frac{-151}{42}\end{matrix}\right.\qquad V=\{(\frac{-9}{14},\frac{-5}{3})\}\)
  2. \(\left\{\begin{matrix}-3x+2y=\frac{-27}{14}\\-6x=y+\frac{-3}{28}\end{matrix}\right.\qquad V=\{(\frac{1}{7},\frac{-3}{4})\}\)
  3. \(\left\{\begin{matrix}-x+3y=\frac{-85}{3}\\6x-6y=50\end{matrix}\right.\qquad V=\{(\frac{-5}{3},-10)\}\)
  4. \(\left\{\begin{matrix}4y=\frac{-217}{13}-2x\\x-2y=\frac{225}{26}\end{matrix}\right.\qquad V=\{(\frac{2}{13},\frac{-17}{4})\}\)
  5. \(\left\{\begin{matrix}3x+2y=\frac{88}{35}\\x-2y=\frac{-144}{35}\end{matrix}\right.\qquad V=\{(\frac{-2}{5},\frac{13}{7})\}\)
  6. \(\left\{\begin{matrix}-3y=\frac{-389}{33}-4x\\-2x+y=\frac{181}{33}\end{matrix}\right.\qquad V=\{(\frac{-7}{3},\frac{9}{11})\}\)
  7. \(\left\{\begin{matrix}6x+3y=\frac{-162}{19}\\x=-3y+\frac{-67}{19}\end{matrix}\right.\qquad V=\{(-1,\frac{-16}{19})\}\)
  8. \(\left\{\begin{matrix}3y=13-4x\\-5x+y=\frac{32}{3}\end{matrix}\right.\qquad V=\{(-1,\frac{17}{3})\}\)
  9. \(\left\{\begin{matrix}6x+4y=\frac{-446}{35}\\-x=-4y+\frac{9}{35}\end{matrix}\right.\qquad V=\{(\frac{-13}{7},\frac{-2}{5})\}\)
  10. \(\left\{\begin{matrix}-6y=\frac{205}{13}+x\\6x+3y=\frac{-1032}{13}\end{matrix}\right.\qquad V=\{(-13,\frac{-6}{13})\}\)
  11. \(\left\{\begin{matrix}-6x-y=\frac{-331}{65}\\4x-4y=\frac{1852}{195}\end{matrix}\right.\qquad V=\{(\frac{16}{15},\frac{-17}{13})\}\)
  12. \(\left\{\begin{matrix}-x+4y=\frac{-39}{5}\\4x=-3y+\frac{263}{20}\end{matrix}\right.\qquad V=\{(4,\frac{-19}{20})\}\)
Oefeningengenerator vanhoeckes.be/wiskunde 2022-05-24 05:38:56